Finansowe mierniki oceny działań marketingowych przedsiębiorstwa - Grzegorczyk, Wojciech (Financial Measures of the Marketing Activities of the Enterprises, 2008)
Between marketing strategy and financial strategy there are mutual interdependencies. This is especially visible when the measurement of effects of marketing actions is necessary. This is when economic coefficients are used above all other means. Economic coefficients include, among others, sales dynamics, return of marketing investment, customer lifetime value, discounted cash flow brand value, cost per sale, cost per point, cost per thousand.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 207-215